Proceedings of the Highly Specialized Seminar on Symmetries in Nuclear Structure:an occasion to celebrate the 60th birthday of Francesco Iachello (Erice, Italy, 23-30 March, 2003) /Andrea Vitturi, Richard F. Casten - Vitturi, Andrea
Includes bibliographical references.